2008
DOI: 10.1097/ccm.0b013e318161f74b
|View full text |Cite|
|
Sign up to set email alerts
|

Prospective study of peripheral arterial catheter infection and comparison with concurrently sited central venous catheters*

Abstract: The incidence of catheter-related bloodstream infection from arterial catheters was low. However, both arterial catheter colonization and rates of catheter-related bloodstream infection were similar to those in concurrently sited and identically managed central venous catheters. By inference, the arterial catheter should be accorded the same degree of importance as the central venous catheter as a potential source of sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
95
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 39 publications
(91 reference statements)
4
95
1
3
Order By: Relevance
“…19,30 Similarly, the femoral site is more susceptible than other sites to the skin flora of the perianal and genitourinary regions. 28,31 Arterial catheters had relatively lower colonization rates than did CVCs but higher colonization rates than did PICCs, supporting the results of our earlier study 32 and the findings of other investigators 33,34 that when systemic sepsis is suspected in a critically ill patient, the arterial catheter should be accorded the same degree of importance as the CVC.…”
Section: Discussionsupporting
confidence: 80%
“…19,30 Similarly, the femoral site is more susceptible than other sites to the skin flora of the perianal and genitourinary regions. 28,31 Arterial catheters had relatively lower colonization rates than did CVCs but higher colonization rates than did PICCs, supporting the results of our earlier study 32 and the findings of other investigators 33,34 that when systemic sepsis is suspected in a critically ill patient, the arterial catheter should be accorded the same degree of importance as the CVC.…”
Section: Discussionsupporting
confidence: 80%
“…In conclusion, our contribution confirms the results of recent and large studies [5,6] reporting higher rate of colonization of peripheral arterial catheters inserted in critically ill patients via the femoral route. However, when the requirement for the best hemodynamic signal outweighs the infectious risks, the femoral route should be favored.…”
supporting
confidence: 82%
“…While Koh et al reported that the risk of catheter-related bloodstream infection associated with radial arterial catheterization is low compared with central venous catheterization, catheter colonization was in fact similar. 26 Dedicated future research into the effects of routine US use for radial artery catheterization on these clinically important complications is warranted and will contribute to our knowledge base.…”
Section: Discussionmentioning
confidence: 99%